In Vitro Callus Development on Immature Leaf Explants of Liberica Coffee (Coffea liberica L. cv. Liberika Tungkal Komposit) by the Application of 2.4-D and BAP - Lizawati Lizawati; Zulkarnain Zulkarnain; Neliyati Neliyati (Biogenesis: Jurnal Ilmiah Biologi, 2020)
Conventional vegetative propagation is the process in which new plants are grown from a variety of sources, seeds, cuttings and other parts of the plants. Therefore, the conventional vegetative propagation of liberica coffee by cutting or grafting of stems is hampered by the limited number of stem or branches, which can be used as propagating materials. In addition, the tissue culture technique is another method used to propagate liberica coffee. This study aims to investigate an efficient protocol for embryogenic callus development from leaf explants of Coffea liberica cv. Liberika Tungkal Komposit. The explants used are immature leaves of fully opened liberica coffee. The medium used was Murashige and Skoog (MS) composition supplemented with vitamins, 3% sucrose and solidified with 0.7% agar, and the medium pH was adjusted to 5.8 ± 0.1. The experiment was arranged in a factorial randomized block design, and the first factor was 2.4-D (2.0, 3.0, 4.0, and 5.0 ppm) and then the second factor was BAP (0.0, 0.5, and 1.0 ppm). The results showed that the application of 2.4-D and BAP significantly improved the distribution of callus proliferation on cultured explants. The use of 2.0 ppm 2.4-D + 1.0 ppm BAP resulted in the fastest callus proliferation (19 days after culture initiation). In general, the application of different levels of 2.4-D and BAP successfully induced friable with nodular morphology callus on young leaf explant of liberica coffee. It is believe that the callus has embryogenic capacity and will undergo embryogenesis when transferred to a suitable medium composition